Notas sobre a nidificação de aves brasileiras raras e/ou pouco conhecidas - Lombardi, Vitor Torga; Faetti, Raisa Gonçalves; D'Angelo Neto, Santos; De Vasconcelos, Marcelo Ferreira; Gussoni, Carlos Otávio Araujo [UNESP] (My University, 2010)
We describe the nests and nesting behaviour of six little-known birds from south-central Minas Gerais, Brazil: Red-and-white Crake Laterallus leucopyrrhus (closed/ovoid/base nest with shells of white eggs), White-throated Woodcreeper Xiphocolaptes albicollis (cavity/without-tunnel/simple/platform nest with two immaculate white eggs), Southern Bristle Tyrant Phylloscartes eximius (closed/globular/lateral nest), Sharp-tailed Tyrant Culicivora caudacuta (high cup/lateral nest with three cream-coloured eggs), White-rumped Monjita Xolmis velatus (low cup/base nest with two immaculate white eggs) and Hellmayr's Pipit Anthus hellmayri (low cup/base nest with three pale brown eggs spotted dark brown).
Notes on the nesting of rare and/or little-known Brazilian birds
Keywords: Anthus hellmayri; Aves; Culicivora caudacuta; Laterallus leucopyrrhus; Phylloscartes eximius; Xiphocolaptes albicollis; Xolmis